2018
DOI: 10.3390/met8070545
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Gallium from Corundum Flue Dust by Two-Stage Alkali Leaching, Carbonation, Acid Leaching and Solvent Extraction Process

Abstract: Flue dust generated during the process of manufacturing corundum is a carrier of critical metal gallium. In this study, a process of alkali leaching-carbonation-acid leaching-solvent extraction was developed to recover and enrich gallium from corundum flue dust. Over 93% of the gallium in corundum flue dust could be recovered through a two-stage alkali leaching process, which consists of 120 min of concentrated alkali leaching in NaOH solution and a subsequent 30-min dilute alkali leaching (after dilution), wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…This makes it difficult to filter the leaching slurry. Meanwhile, the loss of gallium increased due to the adsorption by silica gel [14]. A previous study noted that some rare elements were leached in 3 mol/L acid [13].…”
Section: Effect Of Acid Leaching Time and Hno 3 Concentrationmentioning
confidence: 94%
See 1 more Smart Citation
“…This makes it difficult to filter the leaching slurry. Meanwhile, the loss of gallium increased due to the adsorption by silica gel [14]. A previous study noted that some rare elements were leached in 3 mol/L acid [13].…”
Section: Effect Of Acid Leaching Time and Hno 3 Concentrationmentioning
confidence: 94%
“…Over the past few decades extraction of gallium from coal and CFA has usually followed three main paths: Direct acid leaching [9,10] or alkali roasting followed by acid leaching [11][12][13] or alkali leaching [14]. However, these methods have a number of disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from primary processing, the process of alkaline leaching and precipitation through CO 2 was studied for gallium recovery from industrial by-products. Wen et al [19] investigated extraction from corundum flue dust and found that increasing the alkali concentration and temperature facilitated gallium leaching. In this work, the concentration of NaOH was varied from 35 to 55 wt.% and maximum temperature was set to 90 • C. Depending on alkali concentration, the liquid to solid ratio had a considerable influence on the leaching efficiency of gallium.…”
Section: Primary Gallium Extraction From Bayer Liquormentioning
confidence: 99%
“…However, the high causticity of the hydrofluoric acid and the treatment of fluorine-containing wastewater must be taken into account in this process. A two-stage alkaline leaching, carbonation, acid leaching, and solvent extraction process was proposed in another paper to recover gallium from the CFD collected from a plant in Shanxi Province, China [32], and the overall gallium recovery was acceptable. However, the two-step alkali leaching procedure could be simplified and improved.…”
Section: Introductionmentioning
confidence: 99%